Effects of Additional Amount of Carbon Micro-Coils on the Electrical Properties of Carbon Micro-Coils Composite Sheet as a Tactile Sensor (Journal of Bangladesh Academy of Sciences, 2012)
The morphology and electrical properties, tactile sensing properties of carbon micro-coils  (CMC) composite sheet were examined. Frequency dependence of electrical parameters;  inductance (L), capacitance (C) and impedance (Z) were measured on single and double-helix  composite sheets. It was found that these parameters of carbon micro-coils/polysilicone composites  extensively changed with the additional amount of CMC with polysilicone resine. It was also  observed that the higher additional amount (0 - 10 wt%) of CMC is appropriate for high sensitivity  as a tactile sensor. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12961 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 177-186, 2012